Politik dan Kebijakan Keimigrasian di Indonesia - Hardiyan Honestyman Zamasi; Joan Manuel Vischa; Mike Yakub Sipayung (Universitas Medan Area, 2026)
This study aims to analyze the dynamics of immigration politics and policies in Indonesia from a legal perspective and their implications for security, state sovereignty, and national interests. The research method used is normative juridical with a statutory and conceptual approach. Research data was obtained through a literature review that includes scientific journals, books, and legal documents relevant to immigration policy. The results show that Indonesian immigration policy is based on the principle of selective policy, which aims to filter the entry of foreigners based on aspects of benefits and potential threats to the state. In practice, the implementation of this policy faces various challenges due to globalization, visa-free policies, and international dynamics such as the COVID-19 pandemic and the refugee crisis. Furthermore, immigration law enforcement through administrative measures, such as deportation and deterrence, needs to be aligned with the principles of international law and the protection of human rights. This study emphasizes the importance of adaptive and responsive immigration policy reform to global developments. Strengthening supervision, optimizing the immigration information system, and improving coordination between institutions are strategic steps in realizing a national immigration system that is effective, sustainable, and capable of supporting Indonesia's national interests.